Memory impairment following intentional self-poisoning with benzodiazepines: Should we pay more attention to attention?. (November 2019) - Salles, Juliette; Pariente, Jérémie; Schmitt, Laurent; Lauque, Dominique; Lanot, Thomas; Very, Etienne; Gandia, Peggy; Lemesle, Béatrice; Arbus, Christophe; Giron, Aurélie
Study hypothesis: In cases where patients attempt suicide through intentional self-poisoning, they often ingest drugs such as benzodiazepines that alter the central nervous system and memory. This is problematic, given that experts recommend the recovery of a patient's cognitive capacity before any psychiatric assessment is conducted. A previous pilot study by our group showed that cognitive tests focusing on attention are the most valuable when it comes to determining whether sufficient cognitive recovery has occurred to ensure that patients will remember the assessment after intentional self-poisoning with benzodiazepines. The main aim of our study was to determine cognitive predictors of the recall of the psychiatric assessment after a suicide attempt. The second aim was to determine the threshold for episodic memory. Methods: We recruited 97 patients admitted for intentional self-poisoning. At the time of the psychiatric assessments, we quantified plasma benzodiazepine levels and performed a cognitive assessment. We then used a linear regression model to identify the associations in a control and a benzodiazepine group between cognitive functions and episodic memory scores obtained 24 hours after psychiatric assessment. Results: Our model accounted for 28% and 37%, respectively, of the variance in memory in the control and benzodiazepine groups. The most significant correlations were found for the Wechsler Adult Intelligence Scale coding test in both groups. In the control group, tests such as visual and verbal memory were also associated with recall. Conclusions: Benzodiazepines particularly affect memory by impairing what is remembered of attentional tests. These are, however, the most suitable cognitive tests for predicting recall of the memory assessment.